Reactions of Isoxazoline and Isoxazole Derivatives with Hydraaaazine Hydrate† - Abu-Orabi, S.T.; AL-Hamdany, R.; AL-Momany, L.A.; Ta'an, E.A. (Asian Journal of Chemistry, 2010)
The reaction of cis- or trans-dialkyl-2-isoxazoline dicarboxylate (1a–d, 3a–d,) and dialkyl isoxazole dicarboxylate (5a–d) with hydrazine hydrate afforded the corresponding bis-(hydrazinocarbonyl)-2-isoxazoline and isoxazole derivatives (2a–b, 4a–b and 6a–b) respectively. Short time reaction of di-t-butyl isoxazol dicarboxylate (5e–f) afforded the mono (hydrazinocarbonyl) derivatives (7e–f) which on prolonged heating with hydrazine hydrate afforded (6a–b). On the other hand when the same reaction is conducted with dibenzoylisoxazole (8a–b) and trans-dibenzoyl-2-isoxazoline (10a–b) the cyclized products, pyridazino isoxazole derivatives (9a–b, 11a–b), are formed.